2020
DOI: 10.3390/microorganisms8101586
|View full text |Cite
|
Sign up to set email alerts
|

Yogurt Produced by Novel Natural Starter Cultures Improves Gut Epithelial Barrier In Vitro

Abstract: Yogurt is a traditional fermented dairy product, prepared with starter cultures containing Streptococcus thermophilus and Lactobacillus bulgaricus that has gained widespread consumer acceptance as a healthy food. It is widely accepted that yogurt cultures have been recognized as probiotics, due to their beneficial effects on human health. In this study, we have characterized technological and health-promoting properties of autochthonous strains S. thermophilus BGKMJ1-36 and L. bulgaricus BGVLJ1-21 isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 91 publications
0
15
0
Order By: Relevance
“…Consistent with our study, the protein levels of Beclin 1, ATG5, and LC3B-II were decreased during EPEC infection, whereas EPS upregulated these protein expressions, suggesting that EPS promoted autophagosome synthesis. Notably, the EPS-producing strain Streptococcus thermophilus BGKMJ1-36 was proved that it can trigger autophagy indicated as significantly upregulating the expressions of autophagy-related genes including Beclin 1, ATG5, and LC3B-II [38]. A previous study showed that Lactobacillus johnsonii L531 increased ATG5 protein expression for maintaining the autophagy process to accelerate Salmonella infantis clearance in IPEC-J2 cells [27].…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with our study, the protein levels of Beclin 1, ATG5, and LC3B-II were decreased during EPEC infection, whereas EPS upregulated these protein expressions, suggesting that EPS promoted autophagosome synthesis. Notably, the EPS-producing strain Streptococcus thermophilus BGKMJ1-36 was proved that it can trigger autophagy indicated as significantly upregulating the expressions of autophagy-related genes including Beclin 1, ATG5, and LC3B-II [38]. A previous study showed that Lactobacillus johnsonii L531 increased ATG5 protein expression for maintaining the autophagy process to accelerate Salmonella infantis clearance in IPEC-J2 cells [27].…”
Section: Discussionmentioning
confidence: 97%
“…Bulgarian yoghurt and white brined cheese are rich sources of strains producing exopolysaccharides (EPS), macromolecular compounds known for their anticancer and immunomodulatory activity, as well as the ability to maintain the intestinal barrier by regulating the functions of the gut microbiome [87,88].…”
Section: Exopolysaccharides (Eps)mentioning
confidence: 99%
“…Probiotic lactobacilli and their secreted molecules have a well-described role in the reinforcement of the gut intestinal barrier by increasing expression of tight junction proteins 40 , 41 . As BGMK2-41-mediated C. elegans resistance to both tested pathogens was uncoupled from their CFUs number in the gut, we propose that upregulated expression of clc-1 consequently strengthened the tight junctions, which may be responsible for the observed longevity extension of infected worms.…”
Section: Discussionmentioning
confidence: 99%